1974
DOI: 10.1073/pnas.71.6.2432
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of DNA Synthesis in a Mammalian Cell-Free System by Trypsin Treatment

Abstract: DNA synthesis in a broken cellular preparation of Chinese hamster cells was enhanced approximately 10-fold by a brief trypsin treatment. Alphachywotrypsin also enhanced the, synthesis, whereas Pronase did not. The trypsin appears to be acting on a compopent of the nucleus. Evidence suggests that the trypsin is not removing protein from the DNA, but may be activating the system some other way.Much remains to be learned about DNA replication, especially in eukaryotic systems. The presence of histones, other chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Influence of cell detachment on resumption of cell proliferation. It has been described that trypsin treatment stimulates DNA synthesis in cell-free systems (8,9) and induces DNA synthesis and cell proliferation in contact-inhibited fibroblast cultures (10,24,42). Furthermore, it is known that loosening the attachment of cells to their substratum is required for proliferation (10,24,42).…”
Section: Experiments 3)mentioning
confidence: 99%
“…Influence of cell detachment on resumption of cell proliferation. It has been described that trypsin treatment stimulates DNA synthesis in cell-free systems (8,9) and induces DNA synthesis and cell proliferation in contact-inhibited fibroblast cultures (10,24,42). Furthermore, it is known that loosening the attachment of cells to their substratum is required for proliferation (10,24,42).…”
Section: Experiments 3)mentioning
confidence: 99%
“…Although these effects of trypsin might be expected to influence the capacity of isolated nuclei to synthesize DNA, we did not observe any differences when comparing them with nuclei isolated from cells scraped from glass surfaces. Brown & Stubblefield (1974) also found that DNA synthesis was stimulated about 10-fold in Chinesehamster fibroblast-cell lysates treated with trypsin. DNA synthesis in our BHK-cell nuclei was inhibited by 90 % after exposure to trypsin.…”
Section: Possible Explanationfor the Kinetics Of Dna Synthesismentioning
confidence: 84%